2020
DOI: 10.1111/vec.12972
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of fresh frozen plasma use in 121 cats: 2009–2016

Abstract: Objectives To document indications for fresh frozen plasma (FFP) use in cats, doses administered, and frequency of adverse transfusion reactions (ATR). Design Retrospective observational study from January 2009 to November 2016. Setting Large urban referral and emergency facility. Animals One hundred twenty‐one client‐owned cats that received FFP. Interventions None. Measurements and Main Results Signalment, indication(s), dose, pre‐ and posttransfusion total plasma protein, prothrombin time, activated partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…One study in 36 cats found that coagulopathies were the most common reasons for FFP transfusion (94% of cats) (203). The other study evaluated FFP transfusions in 121 cats and found coagulopathies (83%), hemorrhage (35%), and hypotension (25%) to be the main reasons for administration (204). Median doses reported in dogs are 14 ml/kg (small dogs) and 5 ml/kg (large dogs), due to the administration per unit or ½ unit per dog (197).…”
Section: Use Of Allogenic Plasma Products In Small Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study in 36 cats found that coagulopathies were the most common reasons for FFP transfusion (94% of cats) (203). The other study evaluated FFP transfusions in 121 cats and found coagulopathies (83%), hemorrhage (35%), and hypotension (25%) to be the main reasons for administration (204). Median doses reported in dogs are 14 ml/kg (small dogs) and 5 ml/kg (large dogs), due to the administration per unit or ½ unit per dog (197).…”
Section: Use Of Allogenic Plasma Products In Small Animalsmentioning
confidence: 99%
“…Another study reported median doses of 15-18 ml/kg (198). One study reported median doses of 6 ml/kg in cats (204).…”
Section: Use Of Allogenic Plasma Products In Small Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of transfusion reactions and complications in veterinary studies varies from 0-38%, depending on the species, reaction definitions, and blood products used. [1][2][3][4][5][6][7] While there are consensus recommendations on blood donor screening for prevention of transfusion-transmitted infectious disease, 8 there are no publications that systematically examine the evidence for other prevention strategies. In addition, there is limited information on best practices for monitoring transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Only 33% of the recipients were bleeding at the time of transfusion in this feline study, so most of the transfusions were performed with a prophylactic goal. 4 In another recent study, doses of 2.15–10.85 ml/kg were effective for the treatment of prolonged prothrombin time and/or APTT in cats. Further in vivo prospective studies evaluating different fFFP doses are warranted.…”
Section: Discussionmentioning
confidence: 92%